Commingling of Norway and roof rats with native rodents - Baker, Rex O. (eScholarship, University of California, 1984)
The ecology of plague relies on the intermixing (commingling) of animal hosts and their ectoparasites. There has been a noticeable increase in commingling of rats and ground squirrels in Southern California in recent years. This paper discusses this phenomenon in Los Angeles and Orange Counties, where it occurs, how it results from man's activities, and the ecology of varying locations. The role of fleas as vectors of plague and the intermixing of fleas between hosts are discussed. Action to reduce the incidence of commingling and the threat of plague to the urban society is addressed.